2016
DOI: 10.1111/jog.13025
|View full text |Cite
|
Sign up to set email alerts
|

Live‐born diploid fetus complicated with partial molar pregnancy presenting with pre‐eclampsia, maternal anemia, and seemingly huge placenta: A rare case of confined placental mosaicism and literature review

Abstract: A partial molar pregnancy almost always ends in miscarriage due to a triploid fetus. We describe a rare case of a singleton, partial molar pregnancy with a seemingly huge placenta, which continued to delivery of a live-born diploid baby. A 27-year-old primigravida suffered from severe pre-eclampsia and progressive anemia. The uterus was enormously enlarged for the gestational age. A cesarean section was performed because of deterioration of maternal status at 25 weeks' gestation, when more than 3000 mL blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…An increased incidence could be explained by the greater use of assistive reproductive techniques [8]. There are three types of molar pregnancy with coexisting normal live fetus: the most frequent case is a twin pregnancy with one normal fetus having a normal placenta and another complete mole; the second type is a twin pregnancy with regular fetus and placenta and another partial mole [9]; the third and most uncommon occurrence reported only 19 times in the literature is a singleton normal fetus with partial molar placenta, which is similar to our case [5]. The diagnosis of molar pregnancy with coexisting fetus is difficult.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…An increased incidence could be explained by the greater use of assistive reproductive techniques [8]. There are three types of molar pregnancy with coexisting normal live fetus: the most frequent case is a twin pregnancy with one normal fetus having a normal placenta and another complete mole; the second type is a twin pregnancy with regular fetus and placenta and another partial mole [9]; the third and most uncommon occurrence reported only 19 times in the literature is a singleton normal fetus with partial molar placenta, which is similar to our case [5]. The diagnosis of molar pregnancy with coexisting fetus is difficult.…”
Section: Discussionsupporting
confidence: 75%
“…Interruption of pregnancy is common owing to congenital anomalies like triploidy of the fetuses and severe intrauterine fetal growth restriction due to limited normal functional placental circulation. If the pregnancy does not stop, management of molar pregnancies with an apparently normal fetus remains challenging [5, 14]. The woman must be counseled regarding the maternal and fetal complications: late abortion, vaginal bleeding, mal presentations, preterm labor, persistent gestational trophoblastic disease, severe anemia in the fetus, hyperthyroidism, hypertensive disorders of pregnancy, pulmonary edema, and thromboembolic phenomena [15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, there is usually a clear distinction, both sonographically and pathologically, between the molar and non-molar regions of the placenta [18]. A PubMed research about the third type of molar pregnancy has been reported a few times during the period between 1975 to 2018 finding 7 to 13 cases in the medical literature [8,14], and it has been documented to be more in female fetuses with female:male of approximately 3.5:1 [12]. In this case, a preterm baby girl was delivered with no physical malformations during ultrasound examinations, and a normal karyotype 46XX.…”
Section: Discussionmentioning
confidence: 99%
“…Kawasaki and cols reported a literature search, which yielded 18 cases of a singleton, diploid fetus with partial molar pregnancy. The mean gestational age at delivery was 24.5 +/-6.2 weeks, and fetuses survived outside the uterus in only four cases (22.2%) [12]. Management of molar changes associated with normal appearing fetus still remains challenging, with a high risk for both mother and fetus [5].…”
Section: Discussionmentioning
confidence: 99%